Biomechanical substantiation for tactics of surgical treatment in cases of flexor tendons of the hand fingers damage in the «critical» zone - Kurinnyi, Igor; Lazarev, Igor; Yarova, Maryna; Skyban, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
While in reconstructive surgeries after flexor tendons of the hand fingers damage a question on appropriateness of maintaining of the superficial flexor tendon (subject to its integrity). Purpose: based on biomechanical studies and mathematical analysis of the stress-strain state (SSS) of the fingers̕ flexor apparatus and to substantiate tactics of treatment for patients with isolated flexor tendons of the hand fingers injuries. Methods: Calculations on tension changes in anatomic areas annular ligaments and tendon insertions of superficial and deep flexor tendons depending on the bending angles in the interphalangeal joints were done. Using finite element analysis we built three models: 1 — with intact tendons of superficial and deep flexor tendons, 2 — with damaged superficial flexor tendon, 3 — with damaged deep flexor tendon. Calculations of SSS for structures of flexor fingers apparatus were performed. Results: it was proved that in the absence of superficial flexor tendon at intersegmental flexion angles from 0º to 70º tension in the distal tendon attachment points of the deep flexor and in annular ligaments A3 and A5 increases with the maximum values when bent 70º. We propose a two-stage method of the deep flexor tendon plastic with maintenance of superficial flexor tendon (patent of Ukraine № 85349). Conclusions: in the standard load on the flexion apparatus of the fingers in cases of isolated deep flexor tendon injuries it is advisable to maintain the superficial flexor for prevention of overstrain in the distal point of the deep flexor tendon insertion as well as ligamentous apparatus of the finger (annular ligaments A1–A5).